Thalictrum brevisericeum var. pentagynum (Ranunculaceae), a new synonym of T. uncinulatum from China - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2021)
Based on critical observations on both herbarium specimens (including type material) and living plants in the wild, we demonstrate that Thalictrum brevisericeum var. pentagynum, described recently from Heishui county in northwestern Sichuan province, China, is identical with T. uncinulatum, a widely distributed Chinese species. We therefore reduce T. brevisericeum var. pentagynum as a synonym of T. uncinulatum herein. Lectotypification is proposed for T. uncinulatum.